2013
DOI: 10.1111/dsu.12087
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fibroblast Proliferation In Vitro Using Low-Level Infrared Light-Emitting Diodes

Abstract: BACKGROUND Scars, including hypertrophic and keloidal-type scars, may occur after burns, trauma, or surgery. Despite several treatment options available for scars, few effective, noninvasive modalities exist.Recently, a few small clinical studies revealed the possible benefit of red and infrared (IR) low-level light therapy (LLLT) in scar treatment. One of the important features of scars is proliferation of dermal fibroblasts, but in vitro data regarding the effects of light-emitting diode (LED)-generated IR l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 6 publications
2
18
1
1
Order By: Relevance
“…24,25 To our knowledge, this is the first report of the antiproliferative effect of LED-RL on keloid-derived skin fibroblasts in vitro. We believe that our findings serve as "proof of principle" and may establish the foundation for the translation of these "bench" findings to clinical studies to determine the antifibrotic effects of LED-RL for the treatment of keloids and other cutaneous scarring conditions.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…24,25 To our knowledge, this is the first report of the antiproliferative effect of LED-RL on keloid-derived skin fibroblasts in vitro. We believe that our findings serve as "proof of principle" and may establish the foundation for the translation of these "bench" findings to clinical studies to determine the antifibrotic effects of LED-RL for the treatment of keloids and other cutaneous scarring conditions.…”
Section: Discussionmentioning
confidence: 82%
“…This research builds on our previously reported findings that LED-RL can decrease normal human skin fibroblast proliferation in vitro. 24,25 Herein, we report the effects of LED-RL on keloid-derived human skin fibroblast proliferation and viability in vitro.…”
mentioning
confidence: 99%
“…It has been reported that LED and laser radiation produce similar effects in therapeutic applications Volume 32, Number 4, p. 372-379, 2016 (Chaves et al, 2014;Lev-Tov et al, 2013a;Park and Hong, 2015). LED radiation is clinically advantageous for several reasons, including the ability to irradiate a larger area in a short time (Park and Hong, 2015) safety, less painful, and superior portability which allow for patient use at home, with minimal side effects (Lev-Tov et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…LED radiation is clinically advantageous for several reasons, including the ability to irradiate a larger area in a short time (Park and Hong, 2015) safety, less painful, and superior portability which allow for patient use at home, with minimal side effects (Lev-Tov et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…29 Reduction of fibrosis could be mediated by the beneficial effects of LLLT/PBM on the oxidant/antioxidant balance, 30 downregulation of the profibrotic TGF-b, 20 and inhibition of excessive fibroblast proliferation. 31 Although most LLLT/PBM studies have demonstrated efficacy in management of both acutely and chronically affected tissues, not all LLLT/PBM investigations have yielded positive outcomes. As will be discussed, these divergent results may be attributed to several factors, including dosimetry.…”
mentioning
confidence: 99%